2022
DOI: 10.1021/acs.est.1c08682
|View full text |Cite
|
Sign up to set email alerts
|

Siamese Network-Based Transfer Learning Model to Predict Geogenic Contaminated Groundwaters

Abstract: Exposure to geogenic contaminated groundwaters (GCGs) is a significant public health concern. Machine learning models are powerful tools for the discovery of potential GCGs. However, the insufficient groundwater quality data and the fact that GCGs are typically a minority class in data hinder models to produce meaningful GCG predictions. To address this issue, a deep learning method, Siamese network-based transfer learning (SNTL), is used to estimate the probability that hazardous substances are present in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…This study also identified some key limitations of the proposed method. The experimental results generally showed that the recognition performance of models for the nonbulking sludge category was significantly higher than for the bulking category, mainly due to the difference in sample data volume in different categories . In addition, the collected sludge samples only represent their morphological characteristics at the time of sampling without providing any information about long-term variation in characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This study also identified some key limitations of the proposed method. The experimental results generally showed that the recognition performance of models for the nonbulking sludge category was significantly higher than for the bulking category, mainly due to the difference in sample data volume in different categories . In addition, the collected sludge samples only represent their morphological characteristics at the time of sampling without providing any information about long-term variation in characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A second issue concerns detection, as the accuracy of DL methods relies on the quantity of observational data. Insufficient data may prevent DL from achieving satisfactory precision (Cao et al, 2022); however, even in developed countries with well-established infrastructures, the cost of obtaining a substantial volume of highprecision environmental monitoring data such as that needed for river carbon cycle estimation could hinder the application of DL in some locations (Richards et al, 2023). Moreover, even water quality monitoring networks in developing countries are often limited by financial resources and technical capabilities and so must prioritize resource allocation.…”
Section: Machine Learning Advancesmentioning
confidence: 99%
“…11−13 However, TL was primarily applied to a single task and often overlooks potential relationships that may exist between different end points. 11 Another ML paradigm, MTL, can overcome these limitations. MTL leverages experience from related tasks to facilitate the learning of specific tasks, thereby enhancing prediction accuracy by learning multiple related tasks jointly and reducing the risks of overfitting.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14−16 TL and MTL have been successfully applied separately to construct models for environmentally related end points and were proved to improve model performance. 11,17 It can be inferred that their joint application can further improve the model performance, especially in cases with limited data.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation